Distribution of Karamunting (Rhodomyrthus tomentosa AITON) in Several Regions and Its Secondary Metabolite Content - Yenisbar Yenisbar; Asmah Yani (Journal of Tropical Biodiversity, 2022)
Karamunting (Rhodomyrtus tomentosa Aiton) (fam: Myrtaceae), also called Ceylon cherry, downy rose myrtle, is native to South Asia. It treats diarrhea, dysentery, leukorrhea, hemorrhoids, toothache, infection and bleeding after childbirth, heart, and clears cholesterol. The research was conducted between April and August 2016 in South Sumatra in Padamaran and Tanjung Batu Villages and West Kalimantan in Kawat, Karamunting, and Capkala Villages analyzed the distribution of the karamunting plant and its secondary metabolites. Purposive sampling with the transect method was used. The observation variables analyzed included the species present, the number of individuals of each species, height, DBH, and coverage area. Species Composition, Relative Density (KR), Relative Frequency (FR), Relative Dominance (DR), and Important Value Index (INP) were all instrumental to the data analysis calculation. The findings indicated that there were 48 seedlings and 19 sapling species. The density and frequency were greater than that of other plants at the growth rate of seedlings and saplings. While the distribution was dominant in the Capkala Village, the most abundant phenol of karamunting leaves was discovered in Tanjung Batu Village, plentiful flavonoids in Padamaran Village, and the highest saponins and tannins in Karamunting Village. Furthermore, tannin was plentiful in Capkala Village.